The trail of an eastern deity in the western Himalaya: a study of Lord Jagannath’s temple in the Sirmaur region of Himachal Pradesh - Anjali Verma; Neelam (European Bulletin of Himalayan Research)
This paper explores the multiple agents and processes behind the integration of the cult of Jagannath of Puri into the western Himalayan kingdom of Sirmaur circa 1600–1900. It argues that the transition of the cult from Orissa (now called Odisha) to the hills was crucial to the formation of Sirmaur as a modern Rajput state and that this process was closely assisted by the involvement of politically savvy ritual specialists from Rajasthan. Relying on a combination of a close reading of local histories and on-site interviews, it explores the actions and motivations of Sirmaur’s rulers, their subjects and representatives of devotional Vaishnavism in the establishment of a multi-religious state. The establishment of thakurdwaras associated with Krishna in the kingdom’s core regions during the 18th century illustrates the continual evolution of both rulers and priests towards embracing the cultural changes affecting modern India. The representation of these seemingly disparate elements in a single historical narrative ultimately helps to situate the emergence of Himalayan states within the broader context of state-building in early modern South Asia.